2017
DOI: 10.1002/1873-3468.12784
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive enzymes in the tumor microenvironment

Abstract: Antigen encounter by T lymphocytes induces important metabolic changes. Antitumor T lymphocytes enter in a metabolic competition with tumors, which divert feedback mechanisms of the immune response. Immunosuppressive enzymes, modifying the nutrient availability and leading to the production of toxic catabolites, represent one of these mechanisms, contributing to the metabolic halo in which T lymphocytes evolve during immune responses. Two classes of immunosuppressive enzymes, expressed by the tumor cells or by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 127 publications
(128 reference statements)
0
31
0
Order By: Relevance
“…However, there is increasing evidence suggesting that TDO can be produced by a variety of cancers, including hepatocellular carcinoma, glioma, melanoma, and others (94). In addition, recent studies have demonstrated that certain, specialized myeloid cells can express TDO and contribute to an immunosuppressive microenvironment (95, 96). The exact biologic and molecular basis for such a regulatory myeloid cell subset, however, is unclear.…”
Section: Characteristics Of Immune Tolerancementioning
confidence: 99%
“…However, there is increasing evidence suggesting that TDO can be produced by a variety of cancers, including hepatocellular carcinoma, glioma, melanoma, and others (94). In addition, recent studies have demonstrated that certain, specialized myeloid cells can express TDO and contribute to an immunosuppressive microenvironment (95, 96). The exact biologic and molecular basis for such a regulatory myeloid cell subset, however, is unclear.…”
Section: Characteristics Of Immune Tolerancementioning
confidence: 99%
“…Another class of enzymes are the ectoenzymes expressed on the cell surface of T cells, CD39 and CD73. These dephosphorylate extracellular ATP, which is immunostimulatory, to adenosine, which is immunosuppressive (45). Heterogeneous expression of soluble mediators within organs may also contribute to organ-specific immunostats.…”
Section: Soluble Mediatorsmentioning
confidence: 99%
“…The US FDA has approved the clinical registration applications of IDO inhibitors, in 2016, PF-06840003 in the completed trial NCT02764151; in 2017, NLG802 in NCT03164603 and HTI-1090, respectively, in NCT03208959. Furthermore, combinational regimens with other treatment modalities are under evaluation (80), and some of them such as the phase I/II trial of indoximod combined with temozolomide, have shown promising results in patients with primary malignant brain tumors (NCT02052648). The completion of the safety and efficacy study evaluating indoximod in combination with gemcitabine and nab-paclitaxel in patients with metastatic pancreatic cancer (NCT02077881) revealed a promising activity as shown by the increased in intratumoral CD8+ T-cell density (poster presentation at the annual meeting of the American Society of Clinical Oncology 2018).…”
Section: Enzymes Indolamin 2 3-dioxygenasementioning
confidence: 99%